'It Was the Last Time We'd Start the Summer that Way': Space, Race, and Coming of Age in Colson Whitehead's Sag Harbor. (1st October 2020) - Dawson, Adam
ABSTRACT: This article argues that Colson Whitehead's much understudied coming of age novel Sag Harbor makes an important intervention into the history of the coming of age genre. Sag Harbor is the story of upper-middle class Black boy Benji Cooper, now an adult, narrating a summer he spent at the majority Black beach town of Sag Harbor when he was fifteen years old. Through a series of extended comparative readings to canonical works of coming of age – James Baldwin's If Beale Street Could Talk (1974) and Jeffrey Eugenides' The Virgin Suicides (1993) – I argue that such narratives are often dependent on the freedom whiteness grants to move unimpeded through the world. Benji is only able to follow a 'traditional' coming of age narrative because his class gives him access to a space – Sag Harbor – which is not structured by an overdetermining white gaze. Thus, by aligning Benji with 'traditional' coming of age narratives, Whitehead intervenes in the history of Black coming of age literature, which depicts coming of age for Black youth as learning the limits of Blackness in a society built around whiteness.